Mechanism of self-propulsion in 3D-printed active granular particles. (24th November 2016) - Koumakis, N; Gnoli, A; Maggi, C; Puglisi, A; Leonardo, R Di
Abstract: Active granular particles can harness unbiased mechanical vibrations in the environment to generate directed motion. We provide a theoretical framework that connects the geometrical shape of a three dimensional object to its self-propulsion characteristics over a vertically vibrated plate. We find that a maximally efficient propulsion is achieved for structures having tilted flexible legs forming a characteristic angle with the vertical. Our predictions are verified by experimental observations on a class of 3D printed structures with smoothly varying geometrical features.